1999
DOI: 10.1093/toxsci/47.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of thyroid iodine uptake and organification in rats treated with kojic acid

Abstract: In order to elucidate the mechanisms of reduction of serum thyroid hormones caused by continuous administration of kojic acid (KA) and its thyroid tumor-promotion effects, male F344 rats were given pulverized basal diet containing 0.008%, 0.03%, 0.125%, 0.5%, or 2% KA for 4 weeks. As an untreated control group, additional rats were given basal diet alone for the same period. The thyroid 125I uptake was significantly decreased in the groups receiving 0.03% or more. In addition, significant reduction of organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In a previous study, development of thyroid adenomas was observed in B6C3F1 mice fed a diet containing 1.5 and 3%KA for 20 months (Fujimoto et al, 1998). Proliferative lesions of thyroid follicular cells were also increased in rats fed a diet containing 2 and 4%KA for 12 weeks after DHPN initiation, with marked elevation in serum TSH with decreased serum T3 and T4 apparent from weeks 1 to 12 Tamura et al, 1999b). Moreover, inhibition of iodide uptake causing serum thyroid hormone depression and diffuse follicular cell hypertrophy in the thyroid was observed in rats given 0.03%KA for 4 weeks without DHPN initiation (Tamura et al, 1999a).…”
Section: Introductionmentioning
confidence: 76%
“…In a previous study, development of thyroid adenomas was observed in B6C3F1 mice fed a diet containing 1.5 and 3%KA for 20 months (Fujimoto et al, 1998). Proliferative lesions of thyroid follicular cells were also increased in rats fed a diet containing 2 and 4%KA for 12 weeks after DHPN initiation, with marked elevation in serum TSH with decreased serum T3 and T4 apparent from weeks 1 to 12 Tamura et al, 1999b). Moreover, inhibition of iodide uptake causing serum thyroid hormone depression and diffuse follicular cell hypertrophy in the thyroid was observed in rats given 0.03%KA for 4 weeks without DHPN initiation (Tamura et al, 1999a).…”
Section: Introductionmentioning
confidence: 76%
“…As for the effect of KA on the thyroid gland, it was reported that the dietary administration of KA significantly decreased the levels of serum T3 and T4, while significantly increasing the serum TSH level and thyroid weights, and inhibiting iodine uptake and iodine organification in several studies (Hirose et al, 2001;Tamura et al, 1999;Fujimoto et al, 1999). Recently, we have also reported thyroid weight gain and a morphological change, i.e., follicular epithelial hypertrophy, observed in the thyroid of rats orally administered KA for 4 weeks (Higa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Organic formation of iodine was significantly decreased in the 2% KA group (Table 2). Histopathologically, decreased colloid in the follicles, and hypertrophy/diffuse hyperplasia were apparent in this group 13 . Inhibition of iodine uptake and organic iodine formation in the thyroid gland by kojic acid have also been recently reported by others 14,15 .…”
Section: Methodsmentioning
confidence: 73%
“…Kojic acid (KA), a secondary fungal metabolite produced many species of Aspergillus, Acetobacter, and Penicillium, has bacteriostatic and antioxidative potential. S i n c e i t i n h i b i t s m u s h r o o m t y r o s i n a s e a n d polyphenoloxidase, it has been used as a food additive to prevent enzymic browning of raw crabs and shrimps, and as a skin depigmenting agent in cosmetics 5 . Continuous oral treatment with kojic acid for 20 months in mice resulted in induction of thyroid adenomas in both sexes 6 .…”
Section: Introductionmentioning
confidence: 99%